Noninvasive respiratory support in the perioperative setting: a narrative review - Vetrugno, Luigi; Deana, Cristian; Colaianni-Alfonso, Nicolas; Tritapepe, Fabrizio; Fierro, Carmen; Maggiore, Salvatore Maurizio (Frontiers in Medicine, 2024)
The application of preoperative noninvasive respiratory support (NRS) has been expanding with increasing recognition of its potential role in this setting as a physiological optimization for patients with a high risk of developing atelectasis and postoperative pulmonary complications (PPC). The increased availability of high-performance anesthesia ventilator machines providing an easy way for NRS support in patients with reduced lung function should not be under-evaluated. This support can reduce hypoxia, restore lung volumes and theoretically reduce atelectasis formation after general anesthesia. Therapeutic purposes should also be considered in the perioperative setting, such as preoperative NRS to optimize treatment of patients’ pre-existing diseases, e.g., sleep-disordered breathing. Finally, the recent guidelines for airway management suggest preoperative NRS application before anesthesia induction in difficult airway management to prolong the time needed to secure the airway with an orotracheal tube. This narrative review aims to revise all these aspects and to provide some practical notes to maximize the efficacy of perioperative noninvasive respiratory support.